Kajian Rasa Syukur dan Kepribadian Terhadap Loyalitas Pegawai dengan Budaya Organisasi sebagai Mediasi Variabel - ', Mukhlis; Hadiyati, Ernani; Naser, Jamal Abdul (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
In organizational management, employee loyalty is one aspect that must be improved by the organization to ensure the existence and progress of the organization. Some of the factors that can affect loyalty include gratitude, personality and organizational culture. The study aims to describe and analyze gratitude, personality towards employee loyalty both directly and indirectly through organizational culture as a mediating variable. The research sample amounted to 73 employees. Research location at Al Hidayah Donowarih Islamic Education Park Foundation, Karangploso District, Malang Regency. Data analysis method with Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that the Gratitude, Personality and Organizational Culture variables influence Employee Loyalty. Organizational culture fully mediates personality towards employee loyalty. Advice given to organizations that gratitude is one part of organizational culture. Keywords: Gratitude, Personality, Organizational Culture, Employee Loyalty.